Cardiopulmonary Bypass and AKI: AKI Is Bad, So Let's Get Beyond the Diagnosis - Krawczeski, Catherine D. (Frontiers in Pediatrics, 2019)
It is now well established that AKI is a serious and common complication following cardiopulmonary bypass (CPB) in both children and adults, Adverse outcomes may occur in the short term as well as long term, with higher incidence of chronic kidney disease, increased healthcare utilization and higher frequency of cardiovascular events in patients who develop post-CPB AKI. Despite the advances in our understanding of the pathogenesis of the disease and the improvement in diagnostic tools, our therapeutic options have remained suboptimal. There are multiple challenges in designing a clinical therapeutic AKI trial, including a multi-factorial etiology, difficulties with accurate diagnosis of AKI, achievement of adequate study power, and determination of appropriate outcomes. We are often left with “supportive” care. Studies have shown some benefit to AKI bundles, but adherence to bundle guidelines may be suboptimal. Current best practices should include maintenance of adequate renal perfusion pressure and avoidance of fluid overload, with consideration of early renal replacement therapy. Finally, multi-center trials of AKI therapies are crucial to finding treatment for this devastating complication of CPB.